Single Domain Antibodies Methods and Protocols - Saerens, Dirk.; Muyldermans, Serge; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
The development of the hybridoma technology created the possibility to obtain unlimited amounts of monoclonal antibodies (mAb) with high specificity and affinity for any target and to introduce mAbs in a wide range of applications; however, the bulky size of mAbs, costly production, and cumbersome engineering hampered regularly their streamlined development in some applications.  In Single Domain Antibodies: Methods and Protocols, expert researchers examine single variable domain antibody fragments, referred to as VH, VL, VHH or VNAR. These fragments are the smallest intact antigen-binding fragments that can be produced recombinantly at low cost.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.
From Whole Monoclonal Antibodies to Single Domain Antibodies: Think Small -- Introduction to Heavy Chain Antibodies and Derived Nanobodies -- Overview and Discovery of IgNARs and Generation of VNARs -- Creation of the Large and Highly Functional Synthetic Repertoire of Human VH and Vκ Domain Antibodies -- Preparation of a Naïve Library of Camelid Single Domain Antibodies -- Selection by Phage Display of Single Domain Antibodies Specific to Antigens in Their Native Conformation -- Semi-Automated Panning of Naive Camelidae Libraries and Selection of Single-Domain Antibodies Against Peptide Antigens -- Pichia Surface Display: A Tool for Screening Single Domain Antibodies -- Bacterial Two Hybrid: A Versatile One-Step Intracellular Selection Method -- Intracellular Antibody Capture (IAC) Methods for Single Domain Antibodies -- Selection of Functional Single Domain Antibody Fragments for Interfering with Protein-Protein Interactions Inside Cells: A “One Plasmid” Mammalian Two-Hybrid System -- Cell-Free Selection of Domain Antibodies by In Vitro Compartmentalization -- Selection of VHHs Under Application Conditions -- Isolation and Characterization of Clostridium difficile Toxin-Specific Single-Domain Antibodies -- Selection of VHH Antibody Fragments that Recognize Different Aβ Depositions Using Complex Immune Libraries -- Expression of Single-Domain Antibodies in Bacterial Systems -- Expression of VHHs in S. cerevisiae -- Stable Expression of Chimeric Heavy Chain Antibodies in CHO Cells -- Production of Camel-Like Antibodies in Plants -- Selecting and Purifying Autonomous Human Variable Heavy (VH) Domains -- Solubility and Stability Engineering of Human VH Domains -- Improvement of Proteolytic Stability through In Silico Engineering -- Selection of Human VH Single Domains with Improved Biophysical Properties by Phage Display -- Improvement of Single Domain Antibody Stability by Disulfide Bond Introduction -- Characterization of Single-Domain Antibodies with an Engineered Disulfide Bond -- Affinity Maturation of Single-Domain Antibodies by Yeast Surface Display -- Multivalent Display of Single-Domain Antibodies -- Methods for Determining the PK Parameters of AlbudAbs and of Long Serum Half Life Drugs Made Using the AlbudAb Technology -- Fluorescent Protein Specific Nanotraps to Study Protein-Protein Interactions and Histone-Tail Peptide Binding -- Site-Specific Labeling of His-Tagged Nanobodies with 99mTc: A Practical Guide -- Nanobody-Based Chromatin Immunoprecipitation -- User-Friendly Expression Plasmids Enable the Fusion of VHHs to Application-Specific Tags -- Application of Single Domain Antibodies in Tumor Histochemistry -- Nanobodies as Structural Probes of Protein Misfolding and Fibril Formation -- Molecular Imaging Using Nanobodies: A Case Study -- Case Study on Live Cell Apoptosis-Assay Using Lamin-Chromobody Cell-Lines for High-Content Analysis.
Keywords: Immunology; Antibodies; Immunology; Antibodies